EFEKTIVITAS PENGAWASAN KEPALA SEKOLAH DALAM PROSES PEMBELAJARAN DI SMP NEGERI 6 MUARA BUNGO - Aziz, Padli; Astika, Yulia Wiji; Sari, Mela; Antoni, Feri; Nasir, Muhammad (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
The importance of the headmaster’s role in supervising learning outcomes in order to see and assess and help teachers so that all activities that have been programmed can run effectively and efficiently in accordance with what has been planned. The problems in this study are that the teacher is late in entering the classroom, the teacher has not maximized the Learning Implementation Plan (RPP), the teacher has not provided the right teaching method to students, and the teacher does not take advantage of school facilities such as projectors, because at this time teachers are required to master technology. The aim of this study was to determine the effectiveness, of headmaster supervision in the learning process at SMP Negeri 6 Muara Bungo. The method in this study was a descriptive method with a qualitative approach. The population in this study were teachers and students at SMP Negeri 6 Muara Bungo. Meanwhile, the sample in this study amounted to 10 people. The results of this study indicated that the effectiveness of headmaster supervision in the learning process at SMP Negeri 6 Muara Bungo was effective in improving teacher professionalism used one of the indicators of measuring effectiveness, namely the objective approach. It showed that the impact of teachers both in terms of teaching methods and using media in learning as a support. Based on the instrument / observation sheet from the principal to see and assess the learning process carried out by the teacher in the classroom starting from preliminary activities, core activities, and closing activities.